Material Topics in the CSR Reporting of German and Austrian Banks: An Analysis Taking Into Account Future Reporting Obligations - Sopp, Guido; Schäfer, Philipp (Publishing House of Wroclaw University of Economics and Business, 2025)
[The monograph fits into the wave of changes in the sustainability reporting area and presents the preliminary practices and challenges in the initial phase of the European Sustainability Reporting Standards (ESRS) implementation. The collective findings of the individual chapters show not only the diversity in how companies and financial institutions respond to regulatory change, but also the common issues they face in transforming reporting into a meaningful, transparent, and decision-useful management tool. At the heart of this transformation lies the double materiality concept, which mandates organisations to consider both the financial implications of sustainability issues and broader societal and environmental impacts of business activities. As highlighted in this monograph, the uptake of the double materiality is still immature, and the journey toward the ESRS implementation is in its early stages. A key conclusion is, however, that genuine sustainability cannot be achieved through reporting compliance alone. It requires a change of organisational culture, a realignment of incentives, and a promotion of sustainability not as a burden, but as a strategic pillar for long-term value creation. As the regulatory framework stabilises, the focus must turn to institutional learning, methodological refinement, and stakeholder engagement, ensuring that the sustainability reporting regime will live up to its basic informative role for companies, investors, and society at large. Bringing it all together, tailored for ESG professionals, consultants, auditors, and business leaders, this monograph combines strategic insights with reporting practices to support effective ESG concept implementation. With its clear structure and depth of analysis, it also serves as an ideal foundation for students and researchers in sustainability accounting and reporting, as well as corporate governance. Timely and insightful, this publication stands out as an interesting source for anyone shaping the future of accountable business.] z zapowiedzi
Quote as: Sopp, G., & Schäfer, P. (2025). Material Topics in the CSR Reporting of German and Austrian Banks: An Analysis Taking Into Account Future Reporting Obligations. In J. Dyczkowska (Ed.), European Sustainability Reporting Standards in Action: Context, Implementation, Ramifications (pp. 56-75). Publishing House of Wroclaw University of Economics and Business.
Keywords: double materiality; circular economy; climate change; ESRS; sustainability reporting